Case Report: Intravesical and extravesical urachal cyst in children with lower abdominal pain and hematuria - Mao, Kaiyi; Wang, Leibo; Mao, Yuchen; Shang, Xianhui; Zhou, Guangxu; Zhao, Peng (Frontiers in Pediatrics, 2024)
Bladder urachal cysts in children are a rare form of urachal abnormality. In this paper, we present a case of atypical imaging that presented with lower abdominal pain accompanied by hematuria, resulting in the formation of both internal and external urachal cysts in a child. A 6-year-old male child presented with repeated abdominal pain over a span of 4 days. Color ultrasound and pelvic CT scans revealed a soft tissue lesion on the right anterior wall of the bladder with an unclear boundary from the bladder wall.Voiding Cystourethrography (VCUG) showed no significant abnormalities in the bladder, while routine urine testing was positive for hematuria. A cystoscopy was simultaneously performed with a laparoscopic resection of the urachal cyst.Intraoperative cystoscopy identified the intravesical lesion, which was precisely removed using a cystoscope-assisted laparoscopy. Postoperative pathology confirmed that both extravesicalextracystial and intravesicalintracystial lesions were consistent with a urachal cyst. No complications were observed after the operation, and no recurrence was noted during a six-month follow-up. Therefore, for urachal cysts at the bladder's end, the possibility of intravesical urachal cysts should not be excludeddismissed, especially in patients with microscopic hematuriaendoscopic hematuria. We recommend performing cystoscopy simultaneously with laparoscopic urachal cyst removal to avoid missing intravesical lesions.